Evaluasi Daya Tarik Wisata Lanskap Sejarah Istana Alwatzikhoebillah Sambas Kalimantan Barat - Sabahan Sabahan (Eksos, 2021)
The Alwadzikhoebillah Palace area is a cultural heritage related to the history of ancient Sambas. The landscape of the palace building is in the form of a stage and is located close to the river. Rivers are the main infrastructure in carrying out social and government activities. In addition to government interests, the existence of the Alwadzikhoebillah Palace area near the river is also based on the philosophy of the Malay community who believes that a good building location is a place close to a spring. This study uses quantitative and descriptive methods to analyze the relationship between existing data by looking at the potential and constraints that affect tourism activities. The quantitative method was carried out using a simple scoring technique based on the criteria of MacKinnon et al. (1986) with several modifications adapted to the conditions and research needs to assess the potential as a tourist attraction which consists of several components. This evaluation indicates that the Alwatzikhoebillah Palace area actually has two tourist objects and attractions (67%) in the very potential category (S1) and one tourist object and attraction (33%) in the quite potential category (S2). Objects and tourist attractions in the Alwadzikhoebillah Palace area have good access values. All of these accesses are in good condition, namely in the form of flat asphalt roads with no holes and can be passed by two and four-wheeled vehicles. It's just that in the dining area the ease of access is worth less due to the limited parking area for visitors.